The social patterning of measurement errors in self-reports: Impact on socioeconomic inequalities estimates - Kislaya, Irina (2020)
Resumo da apresentação publicado em Revue d'Épidémiologie et de Santé Publique. 2018;66(Suppl. 5):S364. Disponível em https://www.sciencedirect.com/science/article/pii/S0398762018310472